Episodic memory is emotionally laden memory, requiring amygdala involvement. (2019) - Staniloiu, Angelica; Markowitsch, Hans J.
Abstract: The memory impairment of neurological and psychiatric patients is seen as occurring mainly in the autobiographical-episodic memory domain and this is considered to depend on limbic structures such as the amygdala or the septal nuclei. Especially the amygdala is a hub for giving an emotional flavor to personal memories. Bastin et al. fail to include the amygdala in their integrative memory model.